Imaging-Based Risk Stratification for Recurrence Risk in Women with a History of Peripartum Cardiomyopathy - Ma'ayeh, Marwan; Slivnick, Jeremy A.; McKiever, Monique E.; Garrett, Zachary D.; Lim, Woobeen; Cackovic, Michael; Rood, Kara M.; Bradley, Elisa A. (American Journal of Perinatology, 2021)
Objective Peripartum cardiomyopathy (PPCM) affects 1:1,000 U.S. pregnancies, and while many recover from the disease, the risk of recurrence in subsequent pregnancy (SSP) is high. This study aims to evaluate the utility of left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) to predict the risk of recurrence of PPCM in SSP.Study Design We retrospectively evaluated outcomes in women with a history of PPCM and SSP at a large-volume cardioobstetrics program (2008–2019).Results There were 18 women who had incident PPCM and pursued SSP. Of 24 pregnancies in these women, 8 (33%) were complicated by the development of recurrent PPCM. LVEF ≥ 52% or GLS ≤ −16 was associated with a low risk of recurrent PPCM.Conclusion Approximately one-third of women with PPCM developed recurrent PPCM in SSP. LVEF and GLS on prepregnancy echocardiography may predict the risk of recurrence. Additional studies evaluating risk for recurrence are required to better understand which women are the safest to consider SSP.Key Points
Keywords: peripartum; cardiomyopathy; strain; ejection fraction